FORMULASI TISU BASAH BAWANG MERAH (Allium Cepa var. Ascalonicum) DENGAN MINYAK ADAS (Oleum Foeniculum Vulgare) SEBAGAI KOMPRES DEMAM ALAMI - Nurani Alfiyyah, Zulfa; Ratnasari, Dewi; Helmiawati, Yusi (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2020)
Background: Fever is a condition where the body temperature is above normal which is above 38°C. Fever can be relieved by synthetic medicine and traditional medicine, one of the medicinal plants that can be used in traditional medicine to control fever is red onion (Allium Cepa var. Ascalonicum).   Objective: The purpose of the study is to make wet tissue from red onoin (Allium Cepa var. Ascalonicum) with fennel oil (Oleum Foeniculum Vulgare) as an instant or ready-to-use fever compress containing natural ingredients. Method: This research uses action research method to use research instruments in the form of observation sheets and a questionnaire test preferences. The preparation is made with a composition between red onion: fennel oil (12: 1, 12: 2, 12: 3). Results: Shows the results of a wet tissue preparation that is durable and stable for 3 weeks of storage at room temperature 20°C-25°C by organoleptic test with the proposiation formula most preferred by respondents is formula 3 with the addition of 3 ml of fennel oil which is 84% aroma and 88% color. Conclusion: Wet wipes are stable in storage for 3 weeks at room temperature and the most preferred preparation by the public is the third formula with the addition of fennel oil as much as 3 ml.